2005
DOI: 10.1016/j.gca.2004.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Ca isotope fingerprints of early crust-mantle evolution

Abstract: Ca ratios indistinguishable from our measured modern MORB value (i.e., Ca (3.6) ϳ 0). Greenland samples, however, are very diverse ranging from Ca (3.7) ϭ 0.1 in mafic pillow lavas and felsic sheets from the Isua supracrustal belt, up to very radiogenic signatures ( Ca (3.7) ϭ 2.9) in both mafic rocks of the Akilia association and felsic TTG from the coastal Amîtsoq gneisses.At face value, these results imply the Zimbabwe crust is juvenile whereas most Greenland samples include an earlier crustal component. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…To allow for easier comparison with published data and to best illustrate complementarity between terrestrial reservoirs, δ 44/42 Ca values are converted to δ 44 Ca by multiplying by 2.05 (the kinetic mass law) and are reported relative to BSE [with a recommended value of +0.95‰ relative to SRM915a 14 , which is +0.25‰ relative to SRM915b in this study]. As 40 Ca is not directly measured, the use of MC-ICP-MS for stable Ca isotope analyses precludes the need for radiogenic 40 Ca corrections, which could otherwise lead to significant variations in Archean-aged samples analyzed by thermal-ionization mass spectrometry 35 , 36 , 40 .…”
Section: Methodsmentioning
confidence: 96%
“…To allow for easier comparison with published data and to best illustrate complementarity between terrestrial reservoirs, δ 44/42 Ca values are converted to δ 44 Ca by multiplying by 2.05 (the kinetic mass law) and are reported relative to BSE [with a recommended value of +0.95‰ relative to SRM915a 14 , which is +0.25‰ relative to SRM915b in this study]. As 40 Ca is not directly measured, the use of MC-ICP-MS for stable Ca isotope analyses precludes the need for radiogenic 40 Ca corrections, which could otherwise lead to significant variations in Archean-aged samples analyzed by thermal-ionization mass spectrometry 35 , 36 , 40 .…”
Section: Methodsmentioning
confidence: 96%
“…little variation in its 40 Ca/ 44 Ca ratio through time, whereas the (high K/Ca) continental crust has developed highly radiogenic 40 Ca/ 44 Ca ratios in the early stages of Earth's evolution (Kreissig and Elliott, 2005). Finally the impact of the 4.1-3.8 Ga late heavy bombardment (LHB) on the destruction and the recycling of the Hadean crust (Marchi et al, 2014;Shibaike et al, 2016), and on the composition of the mantle, needs to be carefully considered when developing more realistic models for the continental growth.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These geologically-focused contributions used the K-Ca isotope system to determine the formation age of (i) igneous minerals and rocks DePaolo, 1982, 1989;Shih et al, 1994;Fletcher et al, 1997;Nägler and Villa, 2000), (ii) sedimentary minerals (Baadsgaard, 1987;Gopalan, 2008;Cecil and Ducea, 2010); and more recently also to study (iii) the silicate crust contribution to early Archaean cratons (Kreissig and Elliott, 2005) and the oceanic Ca budget over geological time (Caro et al, 2010). The most recent contribution of Ryu et al (2011), which investigated the Ca isotope systematics during a laboratory-controlled dissolution of Precambrian granite ($1.7 Ga), revealed that the weathering of K-rich minerals can generate large radiogenic 40 Ca enrichments, suggesting that these might be utilized in field-based studies as a unique mineral-specific weathering tracer.…”
Section: Differences Between the Biogeochemical Cycling Of Ca And Srmentioning
confidence: 99%